Direct writing of channels for microfluidics in silica by MeV ion beam lithography - Puttaraksa N. (2014)
The lithographic exposure characteristic of amorphous silica (SiO 2) was investigated for 6.8 MeV 16O3+ ions. A programmable proximity aperture lithography (PPAL) technique was used for the ion beam exposure. After exposure, the exposed pattern was developed by selective etching in 4% v/v HF. Here, we report on the development of SiO 2 in term of the etch depth dependence on the ion fluence. This showed an exponential approach towards a constant asymptotic etch depth with increasing ion fluence. An example of microfluidic channels produced by this technique is demonstrated. © (2011) Trans Tech Publications, Switzerland.